Design and Characterization of PLA Bilayer Films Containing Lignin and Cellulose Nanostructures in Combination With Umbelliferone as Active Ingredient - Iglesias Montes, Magdalena L.; Luzi, Francesca; Dominici, Franco; Torre, Luigi; Cyras, Viviana P.; Manfredi, Liliana B.; Puglia, Debora (Frontiers in Chemistry, 2019)
Poly (lactic acid) (PLA) bilayer films, containing cellulose nanocrystals (CNC) or lignin nanoparticles (LNP) and Umbelliferone (UMB) were extruded and successfully layered by thermo-compression starting from monolayer films. Lignocellulosic nanostructures were used in PLA based film as nanofillers at 3wt.%, while UMB was used as active ingredient (AI) at 15wt. %. The effects of processing techniques, presence, typology and content of lignocellulosic nanoparticles have been analyzed and thermal, morphological, mechanical and optical characterization of PLA nanocomposites have been made. Furthermore, X-ray diffraction (XRD) and Fourier Transform Infrared spectroscopy (FTIR) studies evaluated the presence of nanofillers and AI at chemical level. Bilayer formulations showed a good interfacial adhesion and improved stress at break with respect of PLA monolayers, although they were less stretchable and transparent. Data obtained from thermal, colorimetric and transparency investigations underlined that the presence of lignocellulosic nanofillers and AI in PLA monolayer and bilayer films induced relevant alterations in terms of overall color properties and thermal stability, while antioxidant activity of umbelliferone was enhanced by the addition of lignin in produced materials.